2017
DOI: 10.3389/fimmu.2017.00245
|View full text |Cite
|
Sign up to set email alerts
|

Dectin-1 Compromises Innate Responses and Host Resistance against Neospora caninum Infection

Abstract: Neospora caninum is an intracellular protozoan parasite that has drawn increasing interest due to its association with worldwide repetitive bovine abortions, which cause billionaire losses to the meat and dairy industries annually. Innate immunity plays an important role in infection control, and N. caninum activates the production of inflammatory mediators through toll-like receptors, NOD-like receptors, and mitogen-activated protein kinase signaling pathways. Advances in the knowledge of initial host–parasit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 75 publications
1
15
0
3
Order By: Relevance
“…Host innate immunity is a major player against protozoal infections via inhibiting parasite replication and triggering appropriate adaptive immune responses, which controls the active infections and overcomes subsequent re-exposures ( 6 , 10 ). The recognition of highly conserved sets of molecular patterns [pathogen-associated molecular patterns (PAMPs)] by pattern-recognition receptors (PRRs) of host cells leads to the production of inflammatory cytokines ( 11 ). Previous studies have shown that the toll-like receptor 2 (TLR2), TLR3, and TLR11 innate recognition pathway triggers an inflammatory response to control N. caninum infection ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Host innate immunity is a major player against protozoal infections via inhibiting parasite replication and triggering appropriate adaptive immune responses, which controls the active infections and overcomes subsequent re-exposures ( 6 , 10 ). The recognition of highly conserved sets of molecular patterns [pathogen-associated molecular patterns (PAMPs)] by pattern-recognition receptors (PRRs) of host cells leads to the production of inflammatory cytokines ( 11 ). Previous studies have shown that the toll-like receptor 2 (TLR2), TLR3, and TLR11 innate recognition pathway triggers an inflammatory response to control N. caninum infection ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Portanto, no primeiro capítulo deste trabalho nós buscamos elucidar o papel do receptor imune inato Dectina-1 durante a infecção por P. berghei-ANKA. Uma vez que este receptor já foi descrito como importante no reconhecimento imune frente à infeções causadas por fungos, bactérias (SAIJO et al, 2007;WERNER et al, 2009) e mesmo protozoários como N. caninum e T. gondii filogeneticamente relacionados ao Plasmodium (SILVA et al, 2017).…”
Section: Justificativaunclassified
“…As laminas foram então avaliadas através de microscopia de luz (SILVA et al, 2017). A integridade da barreira hematoencefálica foi determinada pelo método de Azul de Evans conforme descrito previamente (HED et al, 1983).…”
Section: Histopatologia E Integridade Da Barreira Hematoencefálicaunclassified
“…Adicionalmente, um estudo sugeriu que a resposta do hospedeiro contra N. caninum é dependente de TLR3 e da proteína adaptadora TRIF uma vez que o RNA do parasito induz produção de interferon do tipo I dependente de TLR3 (BEITING et al, 2014). O receptor ligante de açúcar Dectina-1 é capaz de favorecer o protozoário, funcionando como um mecanismo de escape o que aumenta a susceptibilidade à infecção, por meio de uma baixa produção de espécies reativas de oxigênio que é letal ao parasito (SILVA, et al, 2017). Além disso não somente receptores de membrana participam da imunidade inata contra N. caninum, mas também o receptor citoplasmático Nod2 que é altamente expresso além de ser recrutado para o vacúolo parasitóforo durante a infecção, particularmente participando do processo inflamatório, aumentando assim a letalidade ao hospedeiro (FERREIRA et al, 2016).…”
Section: Resposta Imune Contra N Caninumunclassified
“…The study of innate immunity against N. caninum has shown the importance of PRRs for the control or resistance to the infection through the induction or inhibition of several chemical mediators such as cytokines (MINEO et al, 2009;MINEO et al, 2010, MOTA et al, 2016SILVA et al, 2017). Here we showed that both TLR3 and MyD88 molecules with siRNA silencing led to reduce the IFNγ production and increased the IL-10, IL-6 and IL-8 production during infection in the endometrial cells studied.…”
Section: The Modulation Of Ifnγ Il-10 Il-6 and Il-8 Production Are mentioning
confidence: 99%